2016
DOI: 10.1007/s13197-016-2390-x
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization, antioxidant and anticancer activities of proteins from four legume species

Abstract: The physicochemical, functional, antioxidant and anticancer properties of protein isolates from the seeds of Soybean (SP), Black soybean (BSP), Adzuki bean (ABP), and Mung bean (MBP) were comparatively characterized. The difference was found in the protein composition and physicochemical properties of the four types of legume proteins, which affected the functional properties and bioactivities. BSP and SP had six predominant proteins with a molecular weight (M W ) range of 20-95 kDa, whereas ABP and MBP showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 25 publications
(50 reference statements)
2
30
0
Order By: Relevance
“…Sharma et al (2014) observed water absorption capacity of 10 different genotypes of golden soybean flours within a range of 94.3 to 119.50ml/100g. Agume et al (2017) and Chen et al (2017) reported higher values for WAC of soybean flour as 313 and 427ml/100g, respectively. Value of water absorption capacity of the present study falls in between the values quoted by Sharma et al (2014) and Chen et al (2017), which may be due to the varietal variation and place of cultivation of soybean.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Sharma et al (2014) observed water absorption capacity of 10 different genotypes of golden soybean flours within a range of 94.3 to 119.50ml/100g. Agume et al (2017) and Chen et al (2017) reported higher values for WAC of soybean flour as 313 and 427ml/100g, respectively. Value of water absorption capacity of the present study falls in between the values quoted by Sharma et al (2014) and Chen et al (2017), which may be due to the varietal variation and place of cultivation of soybean.…”
Section: Resultsmentioning
confidence: 91%
“…Agume et al (2017) and Chen et al (2017) reported higher values for WAC of soybean flour as 313 and 427ml/100g, respectively. Value of water absorption capacity of the present study falls in between the values quoted by Sharma et al (2014) and Chen et al (2017), which may be due to the varietal variation and place of cultivation of soybean. Singh (2017) reported WAC of 257 and 307ml/100g for the raw and malted black soybean whereas Marquezi et al (2017) observed WAC of 130.2 and 137.4 ml/100g for the black varieties of common bean.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The amino acid composition of GP, GPH-T, and GPH-T was analyzed using the method in our previous literature (Chen, Wang, Liu, & Chen, 2017). The amino acids' derivatives were filtered and then determined by HPLC (Beijing Persee General Instrument Co., Ltd, Beijing, China) using an ODS C 18 column (4.6 mm × 250 mm × 5 μm, Kromasil).…”
Section: Amino Acids Compositional Analysis Of Gp Gph-p and Gph-tmentioning
confidence: 99%
“…Additionally, another research group demonstrated that treatment of mice with diethylnitrosamine during a high‐fat diet that contains soy protein isolates suppresses the growth of hepatic tumours, injury and inflammation as compared to mice fed the casein protein (Mercer et al ., ). According to this evidence, proteins, peptides and specific amino acids from soybeans do not only exhibit antioxidant and anti‐inflammatory properties but also have synergistic effects contributing to chemoprevention (Chakrabarti et al ., ; Chen et al ., ).…”
Section: The Chemopreventive Property Of Soy Proteins and Peptidesmentioning
confidence: 97%